السّرد الواقعي والتّاريخ التّخييلي في رواية مجنون الحكم - حمادي, وهيبة (جامعة الوادي - university of Eloued, 2020)
مثلت الرّواية إطارًا ضروريًا لمساءلة التّاريخ وبالنّظر إلى قيامها على التّخييل فلقد استطاعت الأخذ من التّاريخ دون إلزامية الحقيقة، وهذا التّعالق بين الرّواية والتّاريخ سمح بمراجعة الحدود الفاصلة بينهما وتمثل رواية "مجنون الحكم" نموذجا للحوار بين نصين أحدهما قائم على تدوين وتأريخ وتوثيق بكل ما يحمله من حقائق وشكوك والثاني قائم على استرجاع جزء من هذا التّاريخ حتى يساعد على فهم الواقع الحالي، فمجنون الحكم هو نسخة متوفرة حاليا بأشكال مختلفة وأسماء مختلفة ومازال التّاريخ يكرر نماذجه وتأتي الرّواية لتعيد نسج النّموذج واختزال الكثافة النّصية التيّ قدمتها كتب التّاريخ عن الحاكم بأمر الله المنصور، إنّ التداخل بين التّاريخ والسّرد يؤسس لكتابة تعيد ديناميكية التّاريخ إلى الواجهة من أجل فهم الرّاهن، وتفكيك بنية النّص الرّوائي القائم على التّاريخ هو إعادة تركيب لدلالة الواقع الذّي هو في الأصل نتيجة هذا التّاريخ وما الرّواية إلاّ مستوى تخيلي يتملص من المسؤولية التّاريخية وإنتاج رسالة جديدة عن نمطية الحكم في الإرث العربي الإسلامي. History is a textbook full of paradoxes, and because it focuses on the memory of the people, it is necessarily returned to them, and this need is felt only by those who find in the present questions that cannot be answered. The novel represented a necessary framework for the accountability of history and given its bases on imagination, it was able to take history without imposing the truth. This connection between the novel and history allowed the revision of the boundaries between them. The novel of Majnoun al-Hakam represents a model of dialogue between two texts: one based on codification, history and documentation with all its facts and doubts. The second is based on retrieving part of this history to help understand the current reality. 'Majnoun al-Hakam' is a copy currently available in different forms and different names and history is still repeating its models. The novel comes back to rewrite the model and reduce the textual density presented by the history books about the ruler by the order of Allah al-Mansur. The overlap between history and narration establishes a writing that redynamically resurrects history in order to understand the present. The interplay between history and narration establishes a writing that redynamically resurrects history in order to understand the present .
The Real Narrative and the Imaginary Story in the Novel "Majnoun Al- .Hakam" by Bensalem Hamish
مقال
Keywords: لتاريخ، الرواية، الرسالة، التواصل، التناص; history, novel, message, communication, textually.